The War of 1948 : Representations of Israeli and Palestinian Memories and Narratives - Kadish, Alon, 1950-; Sela, Avraham (Book collections on Project MUSE., 2016)
The 1948 War is remembered in this special volume, including aspects of Israeli-Jewish memory and historical narratives of 1948 and representations of Israeli-Palestinian memory of that cataclysmic event and its consequences. The contributors map and analyze a range of perspectives of the 1948 War as represented in literature, historical museums, art, visual media, and landscape, as well as in competing official and societal narratives. They are examined especially against the backdrop of the Oslo process, which brought into relief tensions within and between both sides of the national divide concerning identity and legitimacy, justice, and righteousness of "self" and "other."